Entrepreneurial Behaviour of Agripreneurs in Agro Food Parks - Antony, Rin Rose; Thomas, Allan (Journal of Extension Education, 2020)
The study was conducted in Agro Food Parks (AFPs) of Kerala, to analyse the entrepreneurial behaviour of agripreneurs in AFPs. A sample of 80 respondents was randomly selected from the four functional AFPs. Ex-post facto research design was employed for the study. It was observed that about 66 per cent of the respondents had medium entrepreneurial behaviour. The results of correlation analysis revealed that the entrepreneurial behaviour was positively and significantly related with education, cosmopoliteness, market perception, management orientation, extension orientation, group cohesion, environmental orientation, problem solving ability, credit orientation and economic motivation.